(untitled) (CIPEEX, 2022)
INTRODUCTION: THE AREA OF €‹€‹HEALTH AND HUMANIZATION IS A FORM OF ACTION FORMULATION FOR HEALTH PROFESSIONALS AND MANAGERS, TO IMPROVE HEALTH AND DISEASE PERFORMANCE AND PROCESS. IN ORDER TO DEVELOP A QUALITY AND HUMANIZED HEALTH CARE, ONE MUST TAKE INTO ACCOUNT A CULTURE, THE SOCIAL AND ECONOMIC FACTOR THAT THE PATIENTS ARE INSERTED.OBJECTIVE: TO KNOW THE PERCEPTION ABOUT HUMANIZATION IN CARE, THE DIFFICULTIES ENCOUNTERED AND THE COPING STRATEGIES OF NURSING PROFESSIONALS FROM PUBLIC AND PRIVATE HOSPITALS IN THE INTERIOR OF GOIS. METHOD: DESCRIPTIVE STUDY OF QUALITATIVE APPROACH, BEING THE SAMPLE COMPRISED OF 29 NURSING PROFESSIONALS WHO WORKED IN MALE AND FEMALE WARDS. DATA COLLECTION WAS CARRIED OUT BETWEEN FEBRUARY AND MARCH 2016. THE SEMI-STRUCTURED INTERVIEW WAS APPLIED TO OBTAIN THE DATA, WHICH WERE SUBSEQUENTLY TRANSCRIBED AND ANALYZED BY THE BARDIN CONTENT ANALYSIS TECHNIQUE (2007). RESULTS: THE AGE RANGED FROM 20 TO 50 YEARS AND THE SERVICE TIME FROM 1 TO 13 YEARS. AFTER ANALYZING THE DATA, TWO CATEGORIES EMERGED: "HUMANIZATION OF CARE: PREVIOUS KNOWLEDGE, MEANS OF INFORMATION AND HOSPITAL TRAINING" AND "DIFFICULTIES AND COPING STRATEGIES FOR HUMANIZED CARE". REFERRING TO "PREVIOUS KNOWLEDGE ABOUT HUMANIZATION, THE MEANS OF INFORMATION AND HOSPITAL TRAINING" MOST PARTICIPANTS REPORT PREVIOUS KNOWLEDGE ABOUT HUMANIZATION IN CARE, SCORING IT AS: ADEQUATE WAY TO TREAT THE PATIENT, ENSURE SECURITY, PRESERVE RIGHTS, INDIVIDUALITY AND PRIVACY WITH A HOLISTIC LOOK, GIVE ATTENTION TO COMPLAINTS AND NEEDS. FOR THE PARTICIPANTS TO UPDATE ON THE THEME WERE USED AS MEANS: THE INTERNET THROUGH THE VIDEOS CONFERENCES, TECHNICAL COURSES, GRADUATION, BOOKS, LECTURES, PROTOCOLS AND/OR MANUALS OF THE MINISTRY OF HEALTH.&NBSP; REGARDING TRAINING PERFORMED AT THE INSTITUTION ABOUT HUMANIZATION, IT WAS FOUND THAT: 13 DID NOT PARTICIPATE IN ANY QUALIFICATION, 07 PARTICIPATED IN THE INSTITUTION ITSELF AND 09 IN OTHER INSTITUTIONS OF PREVIOUS EMPLOYMENT.&NBSP; IN THE CATEGORY "DIFFICULTIES AND COPING STRATEGIES FOR THE REALIZATION OF HUMANIZED CARE", THE DIFFICULTIES HIGHLIGHTED TO PERFORM A HUMANIZED CARE WERE: BUREAUCRACY IN THE FILLING OF PAPERS AND PROTOCOLS, LACK OF INPUTS AND EQUIPMENT, EMPLOYEE DEFICIT, WORK OVERLOAD, INCREASED DEMAND FOR PATIENTS IN THE SECTORS, DELAYS IN ATTENDANCE, TECHNOLOGY, LACK OF MANAGEMENT IN THE SECTORS, LACK OF CONTINUING EDUCATION, COMPANIONS AND/OR RELATIVES AND LACK OF COLLABORATION OF INSTITUTIONAL SECTORS. THE STRATEGIES FORMULATED TO MINIMIZE THE DIFFICULTIES WERE: TO PROVIDE ASSISTANCE WITH THE AVAILABLE INPUTS, OPTIMIZE THE TIME, EXCEED THE WORKING HOURS TO PERFORM THE PROCEDURES, PASS ON TO THE MANAGERS EXISTING PROBLEMS, GUIDE THE COMPANIONS AND/OR RELATIVES ABOUT THE PROCEDURES UNDERTAKEN TO MINIMIZE CONFLICTS, IMPROVE COMMUNICATION AND AGILITY OF THE SECTORS FOR BETTER COLLABORATION. CONCLUSION: THE THEME IS QUITE APPROACHED IN THEORY, LEAVING TO BE DESIRED IN THE DAILY LIFE OF HOSPITAL PRACTICE, AND THIS RESULTS IN THE FRAGILITY OF NURSING CARE PROVIDED TO PATIENTS AND RELATIVES IN TERTIARY CARE. THERE IS A GREAT NEED FOR INVESTMENT IN THE PROCESS OF HUMANIZATION OF HEALTH CARE IN THE SUS.